Simulated gastrointestinal digestion of milk caseins containing A1 β-casein does not lead to increased production of inflammatory proteins in intestinal epithelial cells in vitro when compared to milk caseins containing A2 β-casein. - Alan Aitchison; Teagan S. Edwards; Andrew S. Day (Journal of Functional Foods)
Gastrointestinal digestion of bovine milk protein β-casein releases a biologically active peptide β-casomorphin (BCM)-7, which has been associated with increased incidence of non-communicable diseases and negative effects on digestive comfort. In this study, casein isolates containing both β-casein isoforms were enzymatically digested using a previously described method. The digestion products were incubated with intestinal epithelial cells with or without the presence of an inflammatory cytokine, interleukin (IL)-1β, and the effects on inflammatory markers studied. BCM-7 was released from digestion of both β-casein isoforms although higher concentrations were released from A1 β-casein. No difference was found in the effects of the digestion products of each β-casein on gene expression of inflammatory markers interleukin (IL)-8, carcinoembryonic antigen-related cell adhesion molecule (CEACAM)6 or intestinal alkaline phosphatase (IAP). Together, the results of this study do not provide insight for the reported health benefits of milk containing A2 β-casein over milk containing the A1 isoform.